Performance of nano metaclay on chloride diffusion for ultra- high performance concrete - M. F., Md Jaafar; H., Mohd Saman; M. N., Muhd Sidek; K., Muthusamy; N., Ismail (IOP Publishing Ltd, 2021)
The major cause for corrosion of steel reinforcement embedded in concrete due to chloride penetration has been the great research effort. The use of nano metaclay in UHPC increase the strength and helps the formation of micro pores by acting as a filler thus improve the chloride penetration resistance characteristic. The aim of this study is to evaluate the chloride diffusion of UHPC using RCPT and chloride penetration depth. Four (4) series of UHPC comprised of plain UHPC and a series of nanoUHPC incorporating 1%, 3% and 5% of nano metaclay were produced. It is reported that the compressive strength of nano UHPCl exhibits higher strength up to 10% compared to plain UHPC. The results showed that UHPC containing nano metaclay also significantly affect the chloride diffusion coefficient. As regards to the results, inclusion of 1% nano metaclay in UHPC led to noticeable benefit towards strength and chloride resistance.